Low Prevalence of Toxoplasma gondii in Sheep and Isolation of a Viable Strain from Edible Mutton from Central China - Yibao Jiang; Shilin Xin; Yiheng Ma; Heng Zhang; Xu Yang; Yurong Yang (Pathogens, 2023)
Sheep are highly susceptible to Toxoplasma gondii, and miscarriage is the main clinical feature. This study investigated 227 sheep samples (210 myocardial tissues from slaughterhouses, 6 ewe serum samples, 3 aborted fetuses, and 8 dead lambs from veterinary clinics) from central China for T. gondii infection. Antibodies against T. gondii were detected using the modified agglutination test (MAT). PCR was performed to detect T. gondii DNA in the tissue samples. The results showed that four samples were seropositive (MAT titer ≥ 1:100), with a seroprevalence of 1.8% (4/227). The seropositive samples included two myocardial samples from a slaughterhouse, one ewe and its aborted fetus from a veterinary clinic. The results revealed that 7 out of 207 (3.4%) sheep tissue samples were PCR-positive, including two myocardial tissue samples from slaughterhouses, three aborted fetuses, and two lambs from veterinary clinics. Toxoplasma gondii vertical transmission had occurred in two of three pairs of ewes and her pups. One viable T. gondii strain (TgSheepCHn14) was isolated from the myocardial tissues of sheep from a slaughterhouse. Tachyzoites were obtained from cell cultures at 70 days following seeding in the brains and lungs of mice. This strain was non-lethal to Swiss mice. The number of parasite brain cysts in mice decreased with time post-infection (p < 0.05). Overall, the prevalence of T. gondii in the sheep samples was low. Although the samples were scattered, and not from planned collections, the current study detected T. gondii antibodies and DNA in aborted fetuses, indicating that vertical transmission could occur and maintain the parasites in sheep herds without exogenous infection.